From Bonapartism to populism Latin American readings of The l8 Brumaire of Louis Bonaparte - Horacio Tarcus (Латиноамериканский исторический альманах, 2023)
The eighteenth Brumaire of Louis Bonaparte was in 1852 a bumpy edition and a circulation limited to German emigrants in the United States, without the slightest direct impact on the events of contemporary France. The French public only knew a translation in 1891, when Louis Bonaparte's regime had collapsed two decades earlier. However, the work of Karl Marx became a classic in the first decades of the twentieth century, while the notion of Bonapartism transcended its national and epochal context, to become a category of modern political thought thought. With Trotsky's exile in Mexico in 1937, the notion was incorporated into the Latin American political vocabulary to account for Cardenismo and other national-popular regimes that emerged on this continent throughout the twentieth century. After intensive use, the term fell into disuse in the 1980s, being displaced by a surrogate notion, that of populism, elaborated by the Argentine political scientist Ernesto Laclau